Green anti-solvent low-energy-consumption method for preparing perovskite crystal film
By using fluorinated organic solvents as antisolvents, the problems of high toxicity and flammability in the preparation of perovskite thin films have been solved, enabling the safe and low-energy preparation of perovskite crystal thin films and promoting the green development of the perovskite photovoltaic industry.
Patent Information
- Application Number
- CN202411222933.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-07
AI Technical Summary
The antisolvents used in the existing perovskite thin film preparation process are highly toxic, flammable, and can easily reach explosive concentrations in the air, increasing production safety hazards and costs.
Fluorinated organic solvents such as perfluorobutyl ketone and perfluoropentanone are used as antisolvents for the preparation of perovskite crystal thin films. By contacting and annealing with the precursor solution, the transformation of the intermediate phase into perovskite crystals is promoted, avoiding the use of toxic and flammable solvents.
This technology enables the preparation of perovskite thin films using low-toxicity, non-flammable anti-solvents, improving production safety and reducing energy consumption, thus meeting the requirements of green, low-carbon, and sustainable development.
Smart Images

Figure CN119277941A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to a method for preparing a perovskite crystal film with a green anti-solvent and low energy consumption. Background Art
[0002] In recent years, organic-inorganic hybrid perovskite materials have developed rapidly. They have the advantages of high optical absorption coefficient, high carrier mobility, simple solution preparation method, etc., which makes this material widely used in the field of solar cells. The highest efficiency of solar cells using organic-inorganic hybrid perovskite films as light-absorbing layer materials has exceeded 25%.
[0003] In the process of preparing high-quality perovskite films by solution method, anti-solvent bath is an important means to effectively extract non-volatile solvents in the precursor film during annealing and promote the transformation of intermediate phase materials in the precursor film into perovskite crystals.
[0004] At present, the anti-solvents reported in the literature mainly include halogenated hydrocarbons (such as chlorobenzene and chloroform), aromatic hydrocarbons (such as toluene), aliphatic ethers (such as ethyl ether), alcohols (such as 2-propanol and n-butanol), esters (such as ethyl acetate and butyl acetate) and alkane compounds.
[0005] Among them, halogenated hydrocarbons and aromatic hydrocarbons are toxic solvents that are harmful to human health and pollute the environment. The use of toxic solvents will inevitably increase the investment in purification equipment, which will lead to more energy consumption and increased production costs.
[0006] Although the toxicity of anti-solvents such as fatty ethers, alcohols, esters and alkanes is greatly reduced, they all have very high flammability risks and low lower explosion limit concentrations.
[0007] For example, the invention application with publication number CN116390609A discloses a perovskite film and a preparation method thereof and a perovskite solar cell, wherein the anti-solvent is selected from at least one of ethyl acetate, toluene, chlorobenzene, and anisole.
[0008] The invention application with publication number CN116419644A discloses a perovskite film with preferential orientation and high uniformity, and a preparation method and application thereof, wherein the anti-solvent is selected from at least one of toluene (To1), chlorobenzene (CB), ethyl acetate (EA), isopropyl alcohol (IPA), ethanol (EtOH), n-butanol (BuOH), chloroform (THMs), butyl acrylate (BA), o-dichlorobenzene (DCB), anisole (Ani), trifluoromethylbenzene (TFT), ethyl ether (DEE), m-xylene (Xyl), mesitylene (Mesit), n-hexane, diethyl ether, iodobenzene, sec-butanol, and methyl acetate.
[0009] The use of anti-solvents, such as spraying and air knife baths, may cause the local concentration of anti-solvents in the air to reach the lower explosion limit, greatly increasing the potential safety hazards of production. If the production environment is replaced with a fully inert nitrogen environment, safety will be greatly improved, but the production cost will be greatly increased.
[0010] Therefore, the development of antisolvents with low toxicity and high safety has positive significance for the preparation of perovskite films. Summary of the invention
[0011] In view of the above-mentioned deficiencies in the prior art, the present invention provides a method for preparing perovskite crystal films using a green anti-solvent and low energy consumption.
[0012] The present invention firstly provides the application of fluorine-containing organic solvent as anti-solvent in the process of preparing perovskite crystal film.
[0013] Preferably, the fluorine-containing organic solvent is at least one of the following: perfluorobutanone, perfluoropentanone, perfluorohexanone, perfluoroheptanone, perfluorooctanone, pentafluoroethane, hexafluoroethane, heptafluoropropane, perfluoroheptane, perfluorohexadecane, octafluoropropane, and octafluorocyclobutane. Perfluorobutanone is perfluoro-2-butanone, perfluoropentanone is perfluoro-3-methyl-2-butanone, perfluorohexanone is perfluoro (2-methyl-3-pentanone), perfluoroheptanone is perfluoro (2-methyl-3-hexanone), perfluorooctanone is perfluoro (2-methyl-3-heptanone), heptafluoropropane is 1,1,1,2,3,3,3-heptafluoropropane, perfluoroheptane is perfluoro-n-heptane, and perfluorohexadecane is perfluoro-n-hexadecane.
[0014] Introducing fluorinated organic solvents as anti-solvents into the preparation process of perovskite films, on the one hand, these organic substances have low toxicity, are basically harmless to the human body at low concentrations, and their volatiles do not damage the ozone layer; on the other hand, these organic substances are non-flammable, which will effectively improve the safety of the production process. The above advantages are of great significance to the green, low-carbon and sustainable development of the perovskite photovoltaic industry.
[0015] The anti-solvent used in the method for preparing perovskite crystal thin film needs to meet the characteristics of the anti-solvent. On the one hand, it does not dissolve the perovskite, and on the other hand, it can be soluble in the organic solvent in the precursor solution.
[0016] The present invention further provides a method for preparing a perovskite crystal film using a green anti-solvent and low energy consumption, comprising the following steps:
[0017] (1) dissolving lead iodide and hydroiodide in an organic solvent to obtain a precursor solution;
[0018] (2) coating the precursor solution on the substrate to form a wet film;
[0019] (3) contacting the wet film with an anti-solvent, and then annealing to obtain the perovskite thin film material,
[0020] Wherein, the anti-solvent is a fluorine-containing organic solvent.
[0021] In the present application, the fluorinated organic solvent is used as an anti-solvent in the preparation of the perovskite crystal film. The anti-solvent is used to extract the solvent in the wet film prepared in step (2) during the annealing process, which is an important means to promote the transformation of the intermediate phase material in the precursor film into the perovskite crystal. Therefore, the steps of preparing the precursor film in step (1) and step (2) can use the commonly used method steps in the prior art.
[0022] Preferably, the fluorine-containing organic solvent is at least one of the following: perfluorobutanone, perfluoropentanone, perfluorohexanone, perfluoroheptanone, perfluorooctanone, pentafluoroethane, hexafluoroethane, heptafluoropropane, perfluoroheptane, perfluorohexadecane, octafluoropropane, and octafluorocyclobutane. Perfluorobutanone is perfluoro-2-butanone, perfluoropentanone is perfluoro-3-methyl-2-butanone, perfluorohexanone is perfluoro (2-methyl-3-pentanone), perfluoroheptanone is perfluoro (2-methyl-3-hexanone), perfluorooctanone is perfluoro (2-methyl-3-heptanone), heptafluoropropane is 1,1,1,2,3,3,3-heptafluoropropane, perfluoroheptane is perfluoro-n-heptane, and perfluorohexadecane is perfluoro-n-hexadecane. Preferably, in step (1), the hydroiodide is at least one of the following: methylammonium iodide, formamidine iodide, and cesium iodide.
[0023] Preferably, in step (1), the organic solvent is at least one of the following: N,N-dimethylformamide, N,N-dimethylacetamide, formamide, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, ethylene glycol monomethyl ether, isopropyl acetate.
[0024] Preferably, in step (1), when lead iodide and hydroiodide are dissolved in an organic solvent to obtain a precursor solution, the addition ratio of lead iodide to the organic solvent is 100-800 mg:1 ml; the molar ratio of hydroiodide to lead iodide is 1:1-1.15.
[0025] Preferably, in step (2), the coating method used when coating the precursor solution on the substrate is spin coating, spray coating, blade coating, slit coating or screen printing. The coating method used in this application can be a coating method conventionally used in the prior art.
[0026] Preferably, in step (3), the method used when the anti-solvent is brought into contact with the wet film is drip coating, spray coating or air knife coating.
[0027] Preferably, in step (3), the annealing temperature is 30 to 120° C., and the annealing time is 10 seconds to 20 minutes. The annealing step is used to remove the organic solvent, thereby converting the wet film into perovskite. The present invention uses a green, low boiling point, high vapor pressure anti-solvent that is non-toxic to the human body, environmentally friendly, does not damage the ozone layer, and does not produce additional carbon emissions to prepare perovskite films and photovoltaic cells, which is conducive to achieving the green, low-carbon, and sustainable development of the perovskite photovoltaic industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the SEM image of the perovskite thin film material prepared in Example 1.
[0029] Figure 2 The JV curve of a perovskite solar cell prepared using the perovskite thin film material prepared in Example 1 as the active layer. DETAILED DESCRIPTION
[0030] The specific process of preparing perovskite crystal thin films with green anti-solvent and low energy consumption is as follows:
[0031] Dissolve one of methylammonium iodide, formamidine iodide, and cesium iodide, or a mixture thereof, as hydroiodide, together with lead iodide, in an organic solvent to obtain a precursor solution; in the precursor solution, the molar ratio of hydroiodide to lead iodide is 1:1-1.15, the organic solvent is one of N,N-dimethylformamide, N,N-dimethylacetamide, formamide, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, ethylene glycol monomethyl ether, isopropyl acetate, or a mixture thereof, and the lead iodide and the organic solvent are mixed. The ratio of the precursor solution is 100-800 mg: 1 ml; the precursor solution is then coated on the substrate by spin coating, spray coating, scraping coating, slit coating or screen printing to form a wet film, and then the green low-boiling anti-solvent is contacted with the wet film by drip coating, spray coating, scraping coating or air knife blowing coating, wherein the green low-boiling anti-solvent is perfluorobutyl ketone, perfluoropentanone, perfluorohexanone, perfluoroheptanone, perfluorooctanone, pentafluoroethane, hexafluoroethane, heptafluoropropane, perfluoroheptane, octafluoropropane or octafluorocyclobutane. Then, thermal annealing is performed, the annealing temperature ranges from 30 to 120° C., and the annealing time ranges from 10 seconds to 20 minutes.
[0032] The present invention is further described in detail by the following examples:
[0033] Embodiment 1:
[0034] The ITO glass substrate was ultrasonically washed with detergent, acetone, isopropanol, and ethanol for 5 minutes, then rinsed with deionized water and dried. After UV-ozone treatment, a PEDOT:PSS layer with a thickness of about 50nm was prepared by spin coating, and baked at 150°C for 15 minutes before being taken out. Methylammonium iodide and lead iodide were mixed and dissolved in N,N-dimethylformamide, the ratio of lead iodide to N,N-dimethylformamide was 100 mg: 1 ml, and the molar ratio of methylammonium iodide to lead iodide was 1:1, and stirred overnight; the precursor solution was spin-coated on the PEDOT:PSS layer to form a wet film by solution spin coating, and then the anti-solvent perfluorobutyl ketone (perfluoro-2-butanone) was coated on the wet film by drop coating, and then annealed at 30°C for 20 minutes to obtain an organic-inorganic hybrid perovskite thin film material. After the ITO glass covered with PEDOT∶PSS and perovskite layer was quenched in liquid nitrogen, it was observed under a scanning electron microscope (SEM) and the following was obtained: Figure 1 The cross-sectional SEM image of the perovskite film material is shown. After anti-solvent treatment, the perovskite film has a dense structure, good morphology and crystallinity. PCBM and BCP layers are spin-coated on the perovskite film in sequence, and an Ag layer with a thickness of about 100 nm is evaporated to obtain a layered perovskite solar cell. Figure 2 Table 1 and Table 1 show the JV curve and photovoltaic parameters of the perovskite solar cell prepared using the perovskite thin film material prepared in Example 1 as the active layer.
[0035] Table 1
[0036]
[0037] Embodiment 2:
[0038] The ITO glass substrate was ultrasonically washed with detergent, acetone, isopropanol and ethanol for 5 minutes, then rinsed with deionized water and dried. After UV-ozone treatment, a PEDOT:PSS layer with a thickness of about 30nm was prepared by spin coating, and it was baked at 130°C for 20 minutes and then taken out. Formamidine iodide and lead iodide were mixed and dissolved in N, N-dimethylacetamide, the ratio of lead iodide to N, N-dimethylacetamide was 800 mg: 1 ml, and the molar ratio of formamidine iodide to lead iodide was 1: 1.15, and stirred overnight; the precursor solution was sprayed on the PEDOT:PSS layer to form a wet film by solution spraying, and then the anti-solvent perfluoropentanone (perfluoro-3-methyl-2-butanone) was coated on the wet film by air knife blowing method, and then annealed at a temperature of 120°C for 10 seconds to obtain an organic-inorganic hybrid perovskite thin film material. The ITO glass covered with PEDOT:PSS and perovskite layer was quenched in liquid nitrogen and observed under a scanning electron microscope (SEM) to obtain a cross-sectional SEM image of the perovskite film material, which is similar to the following: Figure 1The perovskite film has a dense structure, good morphology and crystallinity. PCBM and BCP layers are spin-coated on the perovskite film in sequence, and an Ag layer with a thickness of about 100 nm is evaporated to obtain a layered perovskite solar cell.
[0039] Embodiment 3:
[0040] The ITO glass substrate was ultrasonically washed with detergent, acetone, isopropanol, and ethanol for 5 minutes, then rinsed with deionized water and dried. After UV-ozone treatment, a PEDOT:PSS layer with a thickness of about 40nm was prepared by spin coating, and it was baked at 140°C for 10 minutes and then taken out. Formamidine iodide, cesium iodide, and lead iodide were mixed and dissolved in formamide, the molar ratio of formamidine iodide to cesium iodide was 9:1, the molar ratio of hydroiodide to lead iodide was 1:1.1, and the ratio of lead iodide to formamide was 200 mg:1 ml, and stirred overnight; the precursor solution was scraped on the PEDOT:PSS layer to form a wet film by a scraping method, and then the anti-solvent perfluorohexanone (perfluoro(2-methyl-3-pentanone)) was coated on the wet film by a spraying method, and then annealed at a temperature of 110°C for 30 seconds to obtain an organic-inorganic hybrid perovskite thin film material. The ITO glass covered with PEDOT:PSS and perovskite layer was quenched in liquid nitrogen and observed under a scanning electron microscope (SEM) to obtain a cross-sectional SEM image of the perovskite film material, which is similar to the following: Figure 1 The perovskite film has a dense structure, good morphology and crystallinity. PCBM and BCP layers are spin-coated on the perovskite film in sequence, and an Ag layer with a thickness of about 100 nm is evaporated to obtain a layered perovskite solar cell.
[0041] Embodiment 4:
[0042] The ITO glass substrate was ultrasonically washed with detergent, acetone, isopropanol, and ethanol for 5 minutes, rinsed with deionized water, and dried. After UV-ozone treatment, a PEDOT:PSS layer with a thickness of about 40 nm was prepared by spin coating, and baked at 120°C for 15 minutes before being taken out. Methylammonium iodide, formamidine iodide, and lead iodide were mixed and dissolved in dimethyl sulfoxide, with the molar ratio of formamidine iodide to methylammonium iodide being 95:5, the molar ratio of hydroiodide to lead iodide being 1:1.05, and the ratio of lead iodide to dimethyl sulfoxide being 300 mg:1 ml, and stirred overnight; the precursor solution was coated on the PEDOT:PSS layer to form a wet film by a slit coating method, and then the anti-solvent perfluoroheptanone (perfluoro(2-methyl-3-hexanone)) was coated on the wet film by a spray coating method, and then annealed at 40°C for 15 minutes to obtain an organic-inorganic hybrid perovskite thin film material. The ITO glass covered with the PEDOT:PSS and perovskite layers was quenched in liquid nitrogen and observed under a scanning electron microscope (SEM) to obtain a cross-sectional SEM image of the perovskite thin film material, which was similar to the following: Figure 1 The perovskite film has a dense structure, good morphology and crystallinity. PCBM and BCP layers are spin-coated on the perovskite film in sequence, and an Ag layer with a thickness of about 100 nm is evaporated to obtain a layered perovskite solar cell.
[0043] Embodiment 5:
[0044] The ITO glass substrate was ultrasonically washed with detergent, acetone, isopropanol, and ethanol for 5 minutes, rinsed with deionized water, and dried. After UV-ozone treatment, a PEDOT:PSS layer with a thickness of about 40 nm was prepared by spin coating, and baked at 140°C for 15 minutes before being taken out. Methylammonium iodide, cesium iodide, and lead iodide were mixed and dissolved in N-methylpyrrolidone, the molar ratio of methylammonium iodide to cesium iodide was 8:2, the molar ratio of hydroiodide to lead iodide was 1:1.08, and the ratio of lead iodide to N-methylpyrrolidone was 400 mg:1 ml, and stirred overnight; the precursor solution was coated on the PEDOT:PSS layer to form a wet film by a slit coating method, and then the anti-solvent perfluorooctanone (perfluoro(2-methyl-3-heptanone)) was coated on the wet film by a wind knife blowing method, and then annealed at a temperature of 50°C for 12 minutes to obtain an organic-inorganic hybrid perovskite thin film material. The ITO glass covered with PEDOT:PSS and the perovskite layer was quenched in liquid nitrogen and observed under a scanning electron microscope (SEM) to obtain a cross-sectional SEM image of the perovskite thin film material, which is similar to the following: Figure 1 The perovskite film has a dense structure, good morphology and crystallinity. PCBM and BCP layers are spin-coated on the perovskite film in sequence, and an Ag layer with a thickness of about 100 nm is evaporated to obtain a layered perovskite solar cell.
[0045] Embodiment 6:
[0046] The ITO glass substrate was ultrasonically washed with detergent, acetone, isopropanol, and ethanol for 5 minutes, rinsed with deionized water, and dried. After UV-ozone treatment, a PEDOT:PSS layer with a thickness of about 40 nm was prepared by spin coating, and baked at 140°C for 15 minutes before being taken out. Methylammonium iodide, formamidine iodide, cesium iodide and lead iodide are mixed and dissolved in ethylene glycol monomethyl ether, wherein the molar ratio of methylammonium iodide, formamidine iodide and cesium iodide is 1:8:1, the molar ratio of hydroiodide to lead iodide is 1:1.12, and the ratio of lead iodide to ethylene glycol monomethyl ether is 500 mg:1 ml, and the mixture is stirred overnight; a slit coating method is adopted to coat the precursor solution on the PEDOT:PSS layer to form a wet film, and then an anti-solvent heptafluoropropane (1,1,1,2,3,3,3-heptafluoropropane) is coated on the wet film by a spray coating method, and then an annealing treatment is performed at a temperature of 90°C for 90 seconds to obtain an organic-inorganic hybrid perovskite thin film material. The ITO glass covered with PEDOT:PSS and perovskite layer was quenched in liquid nitrogen and observed under a scanning electron microscope (SEM) to obtain a cross-sectional SEM image of the perovskite film material, which is similar to the following: Figure 1 The perovskite film has a dense structure, good morphology and crystallinity. PCBM and BCP layers are spin-coated on the perovskite film in sequence, and an Ag layer with a thickness of about 100 nm is evaporated to obtain a layered perovskite solar cell.
[0047] Embodiment 7:
[0048] The ITO glass substrate was ultrasonically washed with detergent, acetone, isopropanol, and ethanol for 5 minutes, rinsed with deionized water, and dried. After UV-ozone treatment, a PEDOT:PSS layer with a thickness of about 40 nm was prepared by spin coating, and baked at 140°C for 15 minutes before being taken out. Methylammonium iodide, formamidine iodide, cesium iodide and lead iodide are mixed and dissolved in a mixed solvent of N,N-dimethylformamide and N-methylpyrrolidone, wherein the volume ratio of N,N-dimethylformamide to N-methylpyrrolidone is 7:3, the molar ratio of methylammonium iodide, formamidine iodide and cesium iodide is 0.5:9:0.5, the molar ratio of hydroiodide to lead iodide is 1:1, and the ratio of lead iodide to organic solvent is 600 mg:1 ml, and the mixture is stirred overnight; a screen printing method is used to coat the precursor solution on a PEDOT:PSS layer to form a wet film, and then an anti-solvent hexafluoroethane is coated on the wet film by a scraping method, and then an annealing treatment is performed at a temperature of 60°C for 10 minutes to obtain an organic-inorganic hybrid perovskite thin film material. The ITO glass covered with PEDOT:PSS and perovskite layer was quenched in liquid nitrogen and observed under a scanning electron microscope (SEM) to obtain a cross-sectional SEM image of the perovskite film material, which is similar to the following: Figure 1The perovskite film has a dense structure, good morphology and crystallinity. PCBM and BCP layers are spin-coated on the perovskite film in sequence, and an Ag layer with a thickness of about 100 nm is evaporated to obtain a layered perovskite solar cell.
[0049] Embodiment 8:
[0050] The ITO glass substrate was ultrasonically washed with detergent, acetone, isopropanol, and ethanol for 5 minutes, rinsed with deionized water, and dried. After UV-ozone treatment, a PEDOT:PSS layer with a thickness of about 40 nm was prepared by spin coating, and baked at 140°C for 15 minutes before being taken out. Methylammonium iodide, formamidine iodide, cesium iodide and lead iodide are mixed and dissolved in a mixed solvent of N,N-dimethylacetamide, dimethyl sulfoxide and isopropyl acetate, the volume ratio of N,N-dimethylacetamide, dimethyl sulfoxide and isopropyl acetate is 7:2:1, the molar ratio of methylammonium iodide, formamidine iodide and cesium iodide is 1:8:1, the molar ratio of hydroiodide and lead iodide is 1:1, and the ratio of lead iodide to organic solvent is 700 mg:1 ml, and stirring is carried out overnight; a precursor solution is coated on a PEDOT:PSS layer to form a wet film by a spin coating method, and then an anti-solvent pentafluoroethane is coated on the wet film by an air knife blowing method, and then an annealing treatment is carried out at a temperature of 70°C for 8 minutes to obtain an organic-inorganic hybrid perovskite thin film material. The ITO glass covered with PEDOT:PSS and perovskite layer was quenched in liquid nitrogen and observed under a scanning electron microscope (SEM) to obtain a cross-sectional SEM image of the perovskite film material, which is similar to the following: Figure 1 The perovskite film has a dense structure, good morphology and crystallinity. PCBM and BCP layers are spin-coated on the perovskite film in sequence, and an Ag layer with a thickness of about 100 nm is evaporated to obtain a layered perovskite solar cell.
[0051] Embodiment 9:
[0052] The ITO glass substrate was ultrasonically washed with detergent, acetone, isopropanol, and ethanol for 5 minutes, rinsed with deionized water, and dried. After UV-ozone treatment, a PEDOT:PSS layer with a thickness of about 30 nm was prepared by spin coating, and baked at 140°C for 20 minutes before being taken out. Methylammonium iodide, formamidine iodide and lead iodide are mixed and dissolved in a mixed solvent of N-methylpyrrolidone, acetonitrile and isopropyl acetate, wherein the ratio of N-methylpyrrolidone, acetonitrile and isopropyl acetate is 7:2.5:0.5, the molar ratio of methylammonium iodide and formamidine iodide is 2:98, the ratio of lead iodide and organic solvent is 450 mg:1 ml, and the molar ratio of hydroiodide and lead iodide is 1:1, and the mixture is stirred overnight; a blade coating method is used to coat the precursor solution on a PEDOT:PSS layer to form a wet film, and then an anti-solvent perfluoroheptane (perfluoro-n-heptane) is coated on the wet film by a spray coating method, and then an annealing treatment is performed at a temperature of 115°C for 20 seconds to obtain an organic-inorganic hybrid perovskite thin film material. The ITO glass covered with PEDOT:PSS and perovskite layer was quenched in liquid nitrogen and observed under a scanning electron microscope (SEM) to obtain a cross-sectional SEM image of the perovskite film material, which is similar to the following: Figure 1 The perovskite film has a dense structure, good morphology and crystallinity. PCBM and BCP layers are spin-coated on the perovskite film in sequence, and an Ag layer with a thickness of about 100 nm is evaporated to obtain a layered perovskite solar cell.
[0053] Embodiment 10:
[0054] The ITO glass substrate was ultrasonically washed with detergent, acetone, isopropanol, and ethanol for 5 minutes, rinsed with deionized water, and dried. After UV-ozone treatment, a PEDOT:PSS layer with a thickness of about 30 nm was prepared by spin coating, and baked at 130°C for 20 minutes before being taken out. Methylammonium iodide, formamidine iodide, cesium iodide, and lead iodide are mixed and dissolved in acetonitrile, the molar ratio of methylammonium iodide, formamidine iodide and cesium iodide is 0.5:8.5:1, the molar ratio of hydroiodide to lead iodide is 1:1.1, and the ratio of lead iodide to acetonitrile is 700 mg:1 ml, and stirred overnight; the precursor solution is sprayed on the PEDOT:PSS layer to form a wet film by a solution spraying method, and then the anti-solvent perfluoroheptane (perfluoro-n-heptane) is coated on the wet film by a wind knife blowing method, and then annealing is performed at a temperature of 80°C for 5 minutes to obtain an organic-inorganic hybrid perovskite thin film material. The ITO glass covered with PEDOT:PSS and the perovskite layer is quenched in liquid nitrogen and observed under a scanning electron microscope (SEM) to obtain a cross-sectional SEM image of the perovskite thin film material, which is similar to the following: Figure 1The perovskite film has a dense structure, good morphology and crystallinity. PCBM and BCP layers are spin-coated on the perovskite film in sequence, and an Ag layer with a thickness of about 100 nm is evaporated to obtain a layered perovskite solar cell.
[0055] Embodiment 11:
[0056] The ITO glass substrate was ultrasonically washed with detergent, acetone, isopropanol, and ethanol for 5 minutes, rinsed with deionized water, and dried. After UV-ozone treatment, a PEDOT:PSS layer with a thickness of about 40 nm was prepared by spin coating, and baked at 140°C for 15 minutes before being taken out. Methylammonium iodide, formamidine iodide, cesium iodide and lead iodide are mixed and dissolved in a mixed solvent of N-methylpyrrolidone and acetonitrile, wherein the volume ratio of N-methylpyrrolidone to acetonitrile is 7.5:2.5, the molar ratio of methylammonium iodide, formamidine iodide and cesium iodide is 0.3:9:0.7, the molar ratio of hydroiodide to lead iodide is 1:1, and the ratio of lead iodide to organic solvent is 500 mg:1 ml, and the mixture is stirred overnight; a screen printing method is used to coat the precursor solution on a PEDOT:PSS layer to form a wet film, and then an anti-solvent octafluoropropane is coated on the wet film by a scraping method, and then an annealing treatment is performed at a temperature of 110°C for 25 seconds to obtain an organic-inorganic hybrid perovskite thin film material. The ITO glass covered with PEDOT:PSS and perovskite layer was quenched in liquid nitrogen and observed under a scanning electron microscope (SEM) to obtain a cross-sectional SEM image of the perovskite film material, which is similar to the following: Figure 1 The perovskite film has a dense structure, good morphology and crystallinity. PCBM and BCP layers are sequentially spin-coated on the perovskite film, and an Ag layer with a thickness of about 100nm is evaporated to obtain a layered perovskite solar cell.
[0057] Embodiment 12:
[0058] The ITO glass substrate was ultrasonically washed with detergent, acetone, isopropanol, and ethanol for 5 minutes, rinsed with deionized water, and dried. After UV-ozone treatment, a PEDOT:PSS layer with a thickness of about 40 nm was prepared by spin coating, and baked at 140°C for 15 minutes before being taken out. Formamidine iodide, cesium iodide, and lead iodide are mixed and dissolved in a mixed solvent of N,N-dimethylformamide and acetonitrile, with a volume ratio of N,N-dimethylformamide to acetonitrile of 7:3, a molar ratio of formamidine iodide to cesium iodide of 97:3, a molar ratio of hydroiodide to lead iodide of 1:1.08, and a ratio of lead iodide to an organic solvent of 300 mg:1 ml, and stirred overnight; the precursor solution is coated on the PEDOT:PSS layer to form a wet film by screen printing, and then the anti-solvent octafluorocyclobutane is coated on the wet film by a scraping method, and then annealed at a temperature of 100°C for 1 minute to obtain an organic-inorganic hybrid perovskite thin film material. The ITO glass covered with the PEDOT:PSS and perovskite layer is quenched in liquid nitrogen and observed under a scanning electron microscope (SEM) to obtain a cross-sectional SEM image of the perovskite thin film material, which is similar to the following: Figure 1 The perovskite film has a dense structure, good morphology and crystallinity. PCBM and BCP layers are spin-coated on the perovskite film in sequence, and an Ag layer with a thickness of about 100 nm is evaporated to obtain a layered perovskite solar cell.
[0059] Embodiment 13:
[0060] The ITO glass substrate was ultrasonically washed with detergent, acetone, isopropanol, and ethanol for 5 minutes, then rinsed with deionized water and dried. After UV-ozone treatment, a PEDOT:PSS layer with a thickness of about 40nm was prepared by spin coating, and baked at 140°C for 15 minutes before being taken out. Cesium iodide and lead iodide were mixed and dissolved in isopropyl acetate, the molar ratio of cesium iodide to lead iodide was 1:1, and the ratio of lead iodide to isopropyl acetate was 700 mg:1 ml, and stirred overnight; the precursor solution was coated on the PEDOT:PSS layer to form a wet film by a scraping method, and then the anti-solvent perfluorohexadecane (perfluoro-n-hexadecane) was coated on the wet film by a wind knife blowing method, and then annealed at 70°C for 6 minutes to obtain an organic-inorganic hybrid perovskite thin film material. The ITO glass covered with PEDOT:PSS and perovskite layer was quenched in liquid nitrogen and observed under a scanning electron microscope (SEM) to obtain a cross-sectional SEM image of the perovskite film material, which is similar to the following: Figure 1 The perovskite film has a dense structure, good morphology and crystallinity. PCBM and BCP layers are spin-coated on the perovskite film in sequence, and an Ag layer with a thickness of about 100 nm is evaporated to obtain a layered perovskite solar cell.
Claims
1. Application of fluorinated organic solvents as anti-solvents in the preparation of perovskite crystal films.
2. The use according to claim 1, characterized in that: The fluorine-containing organic solvent is at least one of the following: perfluorobutyl ketone, perfluoropentanone, perfluorohexanone, perfluoroheptanone, perfluorooctanone, pentafluoroethane, hexafluoroethane, heptafluoropropane, perfluoroheptane, perfluorohexadecane, octafluoropropane, and octafluorocyclobutane.
3. A method for preparing perovskite crystal thin film with green anti-solvent and low energy consumption, characterized in that: The following steps are involved: (1) dissolving lead iodide and hydroiodide in an organic solvent to obtain a precursor solution; (2) coating the precursor solution on the substrate to form a wet film; (3) contacting the wet film with an anti-solvent, and then annealing to obtain the perovskite thin film material, Wherein, the anti-solvent is a fluorine-containing organic solvent.
4. The method for preparing perovskite crystal thin film with green anti-solvent and low energy consumption according to claim 3, characterized in that: The fluorine-containing organic solvent is at least one of the following: perfluorobutyl ketone, perfluoropentanone, perfluorohexanone, perfluoroheptanone, perfluorooctanone, pentafluoroethane, hexafluoroethane, heptafluoropropane, perfluoroheptane, perfluorohexadecane, octafluoropropane, and octafluorocyclobutane.
5. The method for preparing perovskite crystal thin film with green anti-solvent and low energy consumption according to claim 3, characterized in that: In step (1), the hydroiodide is at least one of the following: methylammonium iodide, formamidine iodide, and cesium iodide.
6. The method for preparing perovskite crystal thin film with green anti-solvent and low energy consumption according to claim 3, characterized in that: In step (1), the organic solvent is at least one of the following: N,N-dimethylformamide, N,N-dimethylacetamide, formamide, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, ethylene glycol monomethyl ether, isopropyl acetate.
7. The method for preparing perovskite crystal thin film with green anti-solvent and low energy consumption according to claim 3, characterized in that: In step (1), when lead iodide and hydroiodide are dissolved in an organic solvent to obtain a precursor solution, the addition ratio of lead iodide to the organic solvent is 100-800 mg: 1 ml; The molar ratio of hydroiodide to lead iodide is 1:1 to 1.
15.
8. The method for preparing perovskite crystal thin film with green anti-solvent and low energy consumption according to claim 3, characterized in that: In step (2), the precursor solution is coated on the substrate by a coating method such as spin coating, spray coating, blade coating, slit coating or screen printing.
9. The method for preparing perovskite crystal thin film with green anti-solvent and low energy consumption according to claim 3, characterized in that: In step (3), the anti-solvent is contacted with the wet film by drip coating, spray coating or air knife coating.
10. The method for preparing perovskite crystal thin film with green anti-solvent and low energy consumption according to claim 3, characterized in that: In step (3), the annealing temperature is 30 to 120° C., and the annealing time is 10 seconds to 20 minutes.
Citation Information
Patent Citations
Perovskite thin film, preparation method thereof and perovskite solar cell
CN116390609A
Perovskite film with preferred orientation and high uniformity and preparation method and application thereof
CN116419644A
Cited By
Solvent composition, perovskite thin film and preparation method thereof, and solar cell
CN120957584A
Solvent composition, perovskite thin film and method for preparing the same, solar cell
CN120957584B